Gender and Energy for Space Heating and Cooling - Tuladhar, Prerana (Journal of the Institute of Engineering, 2020)
Energy is one of the crucial aspects now-a-days to be considered from the household chores to the educational, transportation, industrial and many other sectors. Apart from cooking, space heating and cooling also have greater impact as buildings consume about 40% of world’s energy use and major part of energy is used for space heating and cooling [1]. Gender is another aspect that should be taken in to consideration in the energy sector. Discrimination between men and women, either it may be in the knowledge regarding energy sector, profession, application and practices etc. is seen in our society. Therefore, this paper seeks to investigate the impacts of space heating and cooling in the energy consumption pattern of Residential buildings. This paper explores how the gender issues in the energy sector can be addressed and how can it lead towards the sustainable development of the society and then nation. At the same time, paper highlights the changes and improvements in the energy consumption pattern with the enrollment of women in the energy sector. The conclusions are derived from the several literature studies and explorative data analysis with the concern of gender relation with the energy efficiency in the space heating and cooling of residential buildings.